2016
DOI: 10.15244/pjoes/61835
|View full text |Cite
|
Sign up to set email alerts
|

Water Conservation and Nitrogen Loading Reduction Effects with Controlled and Mid-Gathering Irrigation in a Paddy Field

Abstract: Rice is a widely cultivated crop in China and needs a large quantity of water during its entire growth period. Many water-saving irrigation techniques have been developed and widely applied to conserve water in paddy fi elds in recent years. A controlled and mid-gathering irrigation (CMI) regime is one of them, of which the main feature is to maximize the use of rainwater different from the others. The objective of this study was to assess and verify the water conservation and nitrogen pollution reduction effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As a major rice producing country, China has only 19% of the world's rice planting area but 32% of the world's rice production (FAO 2019, http://www.fao.org/faost at/zh/#data). In addition, 65% of annual agricultural water consumption in China was used to irrigate rice plants (Li, Shao, Sheng, Guan, & Xiao, 2016). Water resources play important roles in maintaining the balance of ecosystem, human survival and socioeconomic development.…”
Section: Introductionmentioning
confidence: 99%
“…As a major rice producing country, China has only 19% of the world's rice planting area but 32% of the world's rice production (FAO 2019, http://www.fao.org/faost at/zh/#data). In addition, 65% of annual agricultural water consumption in China was used to irrigate rice plants (Li, Shao, Sheng, Guan, & Xiao, 2016). Water resources play important roles in maintaining the balance of ecosystem, human survival and socioeconomic development.…”
Section: Introductionmentioning
confidence: 99%
“…Reasonable water and fertilizer management could effectively promote rice yield [3] . Previous studies by scholars have found that water-saving irrigation techniques could improve nitrogen fertilizer absorption, and is favorable for nitrogen migration to the growth center, which could promote the rice yield [4][5][6][7] . Liu [8] found that total grains per panicle, productive panicles and thousand grain weight was not decreased obviously compared to conventional irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…At present, 95% of rice is produced 59 under traditional puddled transplanted conditions, which leading to consumption of 60 large amounts of fresh water. Previous studies suggest that rice production consumes 61 about 65% of total agricultural water consumption 2 . However, with the global climate 62 change, the uneven spatial-temporal distribution of precipitation has caused a severe shortage of freshwater resources, and seasonal drought stress has become a crucial abiotic factor restricting the development of traditional puddled transplanted rice production system in Central China [3][4][5] .…”
Section: Introduction 57mentioning
confidence: 99%